ANALISIS PEMASARAN GULA AREN DI DESA PANGU SATU KABUPATEN MINAHASA TENGGARA - Herlina Wakerkwa; Hengki D. Walangitan; Johny S. Tasirin (COCOS, 2019)
ABSTRACT This study aims to describe the marketing channels and marketing margins of palm sugar in Pangu Satu Village. The study was conducted in August to September 2017 using a survey approach with interviews of 11 respondents consisting of producers, collecting traders and final consumers through filling out questionnaires with open questions. Data were analyzed descriptively to describe marketing channels and marketing margins. Furthermore, the results of the study showed that there were 3 marketing channels obtained, i.e. Marketing channel type I producers - final consumers, marketing channel type II producers - merchant traders - end consumers and marketing channel type III producers - merchant traders - supermarkets - end consumers. Furthermore, analysis of type II marketing margins obtained by a continuous marketing margin of 12% to 4%, then the marketing channel III obtained a barrage of marketing margins of 20% to 35%.Key Words: Analysis of Palm Sugar Marketing Channels